2021
DOI: 10.3389/fbuil.2021.629956
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Modelling Assumptions on the Seismic Risk of Industrial Precast Concrete Structures

Abstract: This research evaluates the influence of different modelling assumptions on the global and local seismic risk assessment of code-conforming precast reinforced concrete buildings, specifically single-story industrial buildings. In particular the modelling of the system mass, the overhead crane, the beam-to-column and roof-to-beam connections and the cladding system are investigated. For this purpose, a case study resembling a new industrial building designed in accordance with the current Italian building code … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…The friction coefficient was evaluated following Magliulo et al (2011) for neoprene-concrete friction as a function of the normal stress acting on the sliding surface. For the dowel connections at the beam-column joints and at the roof element-beam joints, the parameters of the force-displacement curve were evaluated in accordance with Bressanelli et al (2021) and Magliulo et al (2021) on the basis of the results of experimental tests and analytical formulations (Dei Poli et al, 1992;Kremmyda et al,2014Kremmyda et al, , 2017Zoubek et al, 2015;Ferreira and El Debs, 2000;Sousa et al, 2020a). The implementation of the dowel connections in OpenSees was carried out by calibrating the ModIMKPeakOriented.…”
Section: Modelling Assumptionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The friction coefficient was evaluated following Magliulo et al (2011) for neoprene-concrete friction as a function of the normal stress acting on the sliding surface. For the dowel connections at the beam-column joints and at the roof element-beam joints, the parameters of the force-displacement curve were evaluated in accordance with Bressanelli et al (2021) and Magliulo et al (2021) on the basis of the results of experimental tests and analytical formulations (Dei Poli et al, 1992;Kremmyda et al,2014Kremmyda et al, , 2017Zoubek et al, 2015;Ferreira and El Debs, 2000;Sousa et al, 2020a). The implementation of the dowel connections in OpenSees was carried out by calibrating the ModIMKPeakOriented.…”
Section: Modelling Assumptionsmentioning
confidence: 99%
“…Similarly, Figure 12 shows the mean values for the buildings with masonry infills (EE1 and EE3) and with external RC cladding panels (EE2 and EE4). This last figure presents also the results of the previous RINTC-N project regarding industrial precast buildings designed in accordance with modern seismic regulations (Magliulo et al, 2018): only the demand-capacity curve for the L'Aquila site (Bressanelli et al, 2021) is shown, due to the same model characteristics and chosen engineering demand parameter (relative displacement of the beam-column connection); indeed, in the previous project (Magliulo et al, 2018) the beamcolumn dowel connection was modelled as elastic and the connection failure was determined during post-processing by looking at the connection load instead of at the connection displacement as carried out herein. It is worth mentioning that the case studies of the previous project were characterized by the presence of external cladding panels and by an additional RC topping at the roof level leading a rigid diaphragm behaviour, while herein the considered structural typology could be characterized either by rigid roof diaphragms (EE1 and EE3), in the case of additional RC topping, or flexible roof diaphragms (EE2 and EE4), in the case of precast roof elements directly connected to the supporting beam through dowels or friction.…”
Section: Pushover and Multi-stripe Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The way to model the contribution of the cladding panels in the PRC building has suffered several improvements in the last years [17,20], from elastic elements mixed with rigid bars to include the initial stiffness, to multiple struts and springs to include the mass and nonlinear behavior of the connections [21], among other strategies. Belleri et al [3] presented a numerical model of horizontal panels, with elastic beams connected to the columns by means of nonlinear springs.…”
Section: Numerical Modelling Of Cladding Panelsmentioning
confidence: 99%
“…The seismic design and assessment of such buildings may be carried out following both traditional and displacement-based approaches (Biondini and Toniolo, 2009;Biondini et al, 2010;Colombo et al, 2016;Belleri, 2017;Torquati et al, 2018;Belleri and Labò, 2021;Bosio et al, 2020;Sousa et al, 2020). Considering the modelling strategies in the case of new buildings, specific considerations on this structural typology can be found in Magliulo et al (2018Magliulo et al ( , 2021, Gajera et al (2021), Bressanelli et al (2019Bressanelli et al ( , 2021, Rodrigues et al (2021), Zoubek et al 2014, De Stefani andScotta (2022). During past earthquakes, the main seismic vulnerabilities observed were related to the loss of support of beam and roof elements, to the failure of RC forks at the top of the columns, to the failure of dowel connections, to the overturning of RC cladding panels among others (Belleri et al, 2015;Bournas et al, 2014;Minghini et al, 2016;Nastri et al, 2017;Palanci et al, 2017;Savoia et al, 2012;Belleri et al, 2017;Scotta et al, 2015;Toniolo and Colombo 2012;Menichini et al, 2020).…”
Section: Introductionmentioning
confidence: 99%